2023
DOI: 10.1111/gfs.12609
|View full text |Cite
|
Sign up to set email alerts
|

Main ecological and environmental factors affecting forage yield and quality in alpine summer pastures (NW‐Italy, Gran Paradiso National Park)

Abstract: Summer pastures in the European Alps play a crucial role in providing high quality forage for grazing livestock and encompass a wide variety of vegetation communities. The main issue of their management is the optimal exploitation of the available forage in relation to environmental constraints, aiming at obtaining the highest forage yield and quality from each vegetation community. In this work, we monitored six different vegetation communities characterized by contrasting topographic features and species com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…The lack of resources for mothers during the lactation period might influence how much energy can be allocated to nursing, with cascading effects on offspring growth. Second, although climate warming can increase plant productivity, Alpine plants are sensitive to heat stress and droughts, and climate warming is expected to decrease forage quality and palatability in Alpine grassland systems [ 8 , 9 ] for nursing mothers and their offspring. Third, ambient temperatures can also strongly influence the nutrient intake of yearling chamois during growth by altering the feeding activity [ 22 ] in young and adults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The lack of resources for mothers during the lactation period might influence how much energy can be allocated to nursing, with cascading effects on offspring growth. Second, although climate warming can increase plant productivity, Alpine plants are sensitive to heat stress and droughts, and climate warming is expected to decrease forage quality and palatability in Alpine grassland systems [ 8 , 9 ] for nursing mothers and their offspring. Third, ambient temperatures can also strongly influence the nutrient intake of yearling chamois during growth by altering the feeding activity [ 22 ] in young and adults.…”
Section: Discussionmentioning
confidence: 99%
“…Our results support previous studies showing the importance of climatic conditions for ungulate growth at high elevations and latitudes [ 17 , 19 , 23 ]. Although ungulates can modify their behaviours by eating at night [ 49 ] or shifting their range to higher elevations [ 7 ] to cope with warming spring and summer temperatures, these changes in behaviour cannot cope with the negative effects of climatic conditions on forage quality and palatability [ 8 , 9 ], which persist throughout the day and can be observed at a wide range of elevation. Hence, studies on the effects of climate warming on the quantity and quality of forage during the time window most sensitive for ungulate growths (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical attributes of pastures and mowed/grazed meadows have rarely been analysed in combination with both PV and floristic-vegetation traits, mainly in the alpine context [155,156]. More often, forage yield and quality have been evaluated through proxies [157][158][159].…”
Section: Discussionmentioning
confidence: 99%
“…Elevated precipitation levels increase above-ground biomass, enabling herders to maintain more livestock at these productive sites, where forage consumption is higher 84 . Furthermore, few studies have shown high grassland carrying capacities during summer, owing to the high foraging value in relatively warm and humid conditions 81 , 85 . The strong relationship between livestock, human population density and proximity to settlements reflects (i) the huge demand for meat in the rural-urban continuum, (ii) the need for people and infrastructure to raise livestock, and (iii) the importance of KZ as an exportation hub 2 , 32 , 75 , 86 .…”
Section: Technical Validationmentioning
confidence: 99%